Comparative Analysis of Concrete Compressive Strength Using OPC Cement and PCC Cement with A Mix of Concrete Additives - Anugrah Anugrah; Hamka Wakkang; Suwardi Setiawan (Politeknik Siber Cerdika Internasional, 2026)
Background: Concrete is one of the most essential construction materials widely used in infrastructure development. In recent years, the cement industry has introduced environmentally friendly products such as Portland Composite Cement (PCC) as an alternative to Ordinary Portland Cement (OPC). Objective: This study aims to analyze the comparative compressive strength and split tensile strength of concrete using OPC and PCC cement, as well as to determine the effect of BetonMix additives on the mechanical performance of concrete. Methods: The research employed an experimental laboratory method. Concrete mix design referred to SNI 7656:2012 with a planned compressive strength of 25 MPa. Mix variations consisted of normal concrete, OPC concrete, OPC + 500 ml BetonMix, and PCC + 500 ml BetonMix. Slump testing followed SNI 1972:2008, while compressive strength testing used cylindrical specimens based on SNI 1974:2011. Results: The findings indicate differences in compressive and split tensile strength between OPC and PCC concrete. The addition of BetonMix improved concrete workability and contributed positively to strength development. The highest compressive strength was achieved by OPC concrete with BetonMix, while PCC with BetonMix also demonstrated good and more economical performance. Conclusion: Both OPC and PCC are suitable as structural binders; however, BetonMix additives enhance mechanical performance. This study provides a practical reference for selecting cement types and additives to produce strong, efficient, and economical concrete.